Acute toxicity of cypermethrin on the juvenile of red claw crayfish Cherax quadricarinatus. (December 2019) - Yuan, Julin; Guo, Jianlin; Wang, Haiyang; Guo, Aihuan; Lian, Qingping; Gu, Zhimin
Abstract: In order to assess the toxicity of Cypermethrin (CYP), the 50% lethal concentration (LC50 ) of CYP on the juvenile of Cherax quadricarinatus is assessed. Meanwhile, the transcription level and the content in the antioxidant and biotransformation enzymes in hepatopancreas and immune enzymes in the serum of C. quadricarinatus exposed to CYP (0.1, 1, 10 and 100 ng·L-1) for 96 h were analyzed to reveal the CYP toxicity and detoxification mechanism. 24, 48, 72, 96 h LC50 were 1305.14, 424.52, 287.10 and 215.99 ng·L-1, respectively. There was no significant change of the content of enzymes at low concentration (0.16 ng·L-1). The fast increase of SOD and CAT content was observed at early stage (24 h), subsequent decreased at later stage of trail at medium concentration (0.32 and 0.63 ng·L-1). However, high concentration (1.25 ng·L-1) of CYP significantly inhibited SOD and CAT content. There was a significant increase in the level of MDA, PC and the content of GPx, EROD, CarE, GST at medium and high concentration after 72 h and 96 h exposure. The Na + -K + -ATPase, PO, ALK content decreased at medium and high concentration, especially at the 72-h and the 96-h exposure. The transcription was altered similarly to enzyme content, but the transcriptional response was generally more immediate than enzymatic response. Heat shock protein ( hsp70 ) and multidrug resistance-associated protein 2 ( abcc2 ) genes were up-regulated. Highlights: 96 h LC50 of CYP to C. quadricarinatus is 215.99 ng/L. Antioxidant and biotransformation enzymes play key roles in scavenging CYP toxicity. Hsp70is an important cellular defense to decrease oxidative damages in crustaceans.